Pengembangan dan Validasi Rancang Bangun Sistem Informasi Surat Elektronik Poliklinik Berbasis Website - Muttaqin Kholis Ali (IICET (Indonesian Institute for Counseling, Education and Therapy), 2021)
Polyclinic at State University of Padang is one of technical services unit or UPT that still uses manual system for documenting medical records and administration. The purpose of this project is to make a design about information system in polyclinic at State University of Padang. It will be an effective project for many activities and also for a process of health services, so that, all of activities in Polyclinic will being computerized. Beside of that, this system also uses online system that will help the patient in the clinic to get good services easily. The system of this design uses a PHP's programming language with Framework Codeigniter. Moreover, the design of this information system in the clinic also uses Relational Database Management System (RDBMS) MySQL. Designing and Planning this project uses Bootstrap CSS Framework that functioning to make the system more dynamist and responsive. The output of this project in the clinic at State University of Padang is a system that will fulfill the requirements of health services by an online system. And for an employee, this system is useful to make a monthly or yearly report, so that their job will be easier than before. However, the designing and planning of information systems in that clinic still needing a development in many aspects to get the maximum result. The development of this project will include such as a system or even the people around the clinic at State University of Padang.